A sodium superionic chloride electrolyte driven by paddle wheel mechanism for solid state batteries - Rui Li; Kaiqi Xu; Shenhao Wen; Xiaohan Tang; Zheyu Lin; Xia Guo; Maxim Avdeev; Zhizhen Zhang; Yong-Sheng Hu (Nature Communications)
Abstract Halides are promising solid electrolytes due to their high ionic conductivity and high oxidation potential. Here we report a superionic chloride material, NaTaCl6, which exhibits a high ionic conductivity of 3.3 mS cm−1 at 27 °C, being two-orders of magnitude higher than that of NaNbCl6 (0.01 mS cm−1). The considerably higher conductivity exhibited by NaTaCl6 vs. NaNbCl6 arises from the more facile rotational/reorientational dynamics of the [TaCl6] polyanions in comparison to the [NbCl6] anions. [TaCl6] polyanion rotation is readily activated while [NbCl6] polyanion reorientation is hindered at room temperature but can be turned on as the temperature increases or under prolonged mechanical milling. The higher degree of structural disorder exhibited by NaTaCl6 compared to NaNbCl6—likely attributed to its greater mechanical and phonon softness—is found to contribute to the more pronounced [TaCl6] anion rotation. Anion rotation is coupled with, and facilitates, macroscopic Na+-ion diffusion. As a result, enhanced rotational dynamics are directly correlated with the higher Na+-ion conductivity observed in NaTaCl6. The high ionic conductivity, combined with its electrochemical stability against positive electrode materials, enables good rate capability and long-term cycling performance in solid-state cells. These findings provide insights into ion transport mechanism in the newly emerging halide solid electrolytes.